KARAKTERISTIK MISI KELUARGA DALAM PERSPEKTIF PERJANJIAN LAMA - Gernaida Krisna R. Pakpahan (Sekolah Tinggi Teologi Ekumene Jakarta., 2020)
According to Barna's research, 51% of the church did not understand the Great Commission. Though the church is called to carry out its witnessing duties in this world. The church serves God's people and builds communities that witness and feel the presence of Christ. In order to understand this calling, it is necessary to study the role of Israelites which also had the mission aspect in the Old Testament. The election of Israel as the people of God means that they also have a mission, as an agent of God’s mission to the world. This concept can be seen within the history of the life of Adam until the people of Israel, where God had given the mandate to become a blessing for the world. This research then will elaborate the calling and mission concept within the Old Testament, especially the chosen characters in it. In that context, every character in the Old Testament had their own calling to do God’s mission as their life goal. They all have the same characteristic that is their life goal is to bring other or people to enjoy the blessing of God as God’s people. In that way, the people of God will live in his holiness.